Assessing the impacts of domesticated versus wild ungulates on terrestrial small mammal assemblages at Telperion Nature Reserve, South Africa. Issue 1 (30th April 2018) - Gumbi, Bonginkosi C; Shapiro, Julie T; Mahlaba, Themba; McCleery, Robert; MacFadyen, Duncan; Monadjem, Ara
Abstract : Grazing by large mammals alters vegetation physiognomy, consequently changing habitat suitability for small mammal communities. We investigated the response of terrestrial small mammals to grazing by wild and domesticated ungulates at the boundary of a protected area (Telperion Nature Reserve) and surrounding cattle ranches in Mpumalanga, South Africa over two seasons. Fifteen paired grids were set on either side of the boundary fence at which small mammals were trapped in Sherman live traps placed flat on the ground. A total of 11 760 trap nights resulted in the capture of 187 animals belonging to 14 species (11 rodents, two shrews and one elephant shrew). The small mammal communities in grasslands grazed by domesticated or wild ungulates were similar in abundance, species richness, diversity and demographic parameters, likely due to the fact that vegetation structure of the two grazing systems was also similar. We used generalised linear models to show that rock and grass cover were plausible predictors of small mammal abundance in this system. Rock cover showed a positive relationship with small mammal abundance whilst grass cover showed a negative relationship. Our observations suggest that at the scale of our study and with the current stocking densities, wild and domesticated ungulates have similar impacts on the small mammal community.